A new, cheap method to reduce bird mortality from window collisions (UNED Research Journal, 2018)
Many methods to prevent bird deaths at windows are ineffective, and some useful methods are expensive or displeasing. Here we offer, for free download, an image that ended bird accidents on large windows near a tropical cloud forest area, and propose hypotheses for its experimental evaluation
Keywords: reduction of bird mortality; predator-avoidance behavior; reaction of birds to cats